A microanalysis of trade finance: German bank entry and coffee exports in Brazil, 1880–1913 - Kisling, W (Oxford University Press, 2019)
The trade-finance nexus has enjoyed increasing interest in recent economic studies, but empirical evidence is scarce and studies from a historical perspective seem missing. This study analyses the effect of German bank entry on Brazilian coffee exports between 1880 and 1913 using firm-level data. I create an original data set on the yearly quantities of exported coffee and the credit received from the German Brasilianische Bank für Deutschland by export houses in Brazil. Using a difference-in-difference approach, I find that Brasilianische eased previously existing credit constraints, and that companies financed by Brasilianische exported significantly more than those that were not.